The Best Laid Plans: An Assessment of the Varied Consequences of New Technologies for Crime and Social Control. - Byrne, James M. (Federal Probation, 2008)
Technological advances and innovations have been variously described as a cause of crime and a solution to the ongoing problem of crime. Certainly, it is important to consider technology in terms of crime prevention and crime control, two areas where technology has the potential to make a difference. However, it appears that technological advances have resulted in new opportunities for crime, new techniques for committing crime, and new categories of criminals and victims. Moreover, technology has the power to divert resources from traditional methods of crime prevention that could provide greater safety without many of the complications associated with technology. Those complications include the issue of privacy versus safety; coercive technology; and public versus private-sector control of justice.